Physiological Characteristics of Weeds in Organic and Conventional Arabica Coffee Plantations in Bener Meriah Regency - N, Mutiara; Badhawi, Badhawi; Hafifah, Hafifah; Nasruddin, Nasruddin; Yusra, Yusra (Malikussaleh University, Aceh, Indonesia, 2025)
This study aims to determine the diversity and differences of weed species found in organic and conventional Arabica coffee plantations in Bener Meriah Regency. Weeds are a limiting factor in crop productivity as they compete for nutrients, water, and sunlight. The research employed a survey method using 50 cm × 50 cm quadrants at four sampling points in each plantation type. Data were quantitatively analysed based on density, frequency, and dry weight, and Shannon-Wiener diversity and Sorensen similarity indices were calculated. The results identified 12 weed species, with Bidens pilosa L. as the most dominant. The diversity index was higher in organic plantations (H' = 1.8) than in conventional ones (H' = 1.4), while the weed species similarity index between the two systems was only 42%, indicating substantial differences. Weed chlorophyll content was also generally higher in organic plantations. These findings provide a scientific basis for developing targeted weed management strategies tailored to each plantation system.